Pengaruh Work Life Balance dan Loyalitas Kerja Terhadap Kinerja Karyawan - Derry Wijaya; Ali Jufri; Risdianto (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the influence of Work Life Balance and Work Loyalty on Employee Performance at PT. Sudinar Artha. The research approach used is quantitative with a survey method. Data were collected through questionnaires distributed to 37 respondents, then analyzed using multiple linear regression with the help of SPSS 22. The results of the study indicate that Work Life Balance has a positive and significant effect on employee performance. The better the balance between work and personal life that employees feel, the higher their performance will be. In addition, Work Loyalty has also been proven to have a positive and significant effect on employee performance. Loyal employees tend to be more responsible, dedicated, and committed to achieving company targets. Simultaneously, Work Life Balance and Work Loyalty have a strong influence on employee performance. This study recommends companies to implement a balanced working hours policy, improve the reward and compensation system, pay attention to employee welfare, and build a work culture that supports loyalty so that employee performance can continue to improve sustainably.